2008
DOI: 10.1186/1743-422x-5-134
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute encephalitis syndrome in Western industrialised and tropical countries

Abstract: Background: As part of efforts to control Japanese encephalitis (JE), the World Health Organization is producing a set of standards for JE surveillance, which require the identification of patients with acute encephalitis syndrome (AES). This review aims to provide information to determine what minimum annual incidence of AES should be reported to show that the surveillance programme is active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 45 publications
(123 reference statements)
0
94
0
3
Order By: Relevance
“…6 In a cohort study by Tom Soloman et al WHO JE surveillance standard study focus was on JE Positive or Negative or AES unknown mortality was 18.68% in JE positive cases which is almost similar to this study. In 22% cases AES Unknown diagnosis was made, while in this study AES Unknown was found in 3.2% 7 . The incidence of JE positive case is 22.04% in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…6 In a cohort study by Tom Soloman et al WHO JE surveillance standard study focus was on JE Positive or Negative or AES unknown mortality was 18.68% in JE positive cases which is almost similar to this study. In 22% cases AES Unknown diagnosis was made, while in this study AES Unknown was found in 3.2% 7 . The incidence of JE positive case is 22.04% in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…Viruses are the most common causative agents of AES, though bacteria, fungi, parasites, and toxins have also been implicated in its etiology. The incidence of AES varies from 0.9 per 100,000 adults in Nigeria, to 185 per 100,000 adults for a rural population in Nepal during an outbreak of Japanese encephalitis (JE) (1). In India, it has been estimated that a population of 375 million people residing in 171 endemic districts of 17 states are at a risk of acquiring AES (2).…”
Section: Introductionmentioning
confidence: 99%
“…The surveillance consists of identifying patients with acute encephalitis syndrome (AES), and then classifying the patients according to the results of laboratory diagnostic tests. 11 Transmission is seasonal and mainly related to rainy season in south-east Asia region. 12 Our aim is to study the clinical features of AES in relation with the epidemiological aspects in our study area so that by understanding the main epidemiological features of these infections would assist clinicians in formulating etiological hypothesis, in the event of laboratory findings being inconclusive.…”
mentioning
confidence: 99%